White Space Communication:Advances, Developments and Engineering Challenges - Mishra, Amit Kumar (Springer, 2015)
This monograph presents a collection of major developments leading toward the implementation of white space technology - an emerging wireless standard for using wireless spectrum in locations where it is unused by licensed users. Some of the key research areas in the field are covered. These include emerging standards, technical insights from early pilots and simulations, software defined radio platforms, geo-location spectrum databases and current white space spectrum usage in India and South Africa.